2021
DOI: 10.7717/peerj.11743
|View full text |Cite
|
Sign up to set email alerts
|

Test-retest reliability of a functional electromechanical dynamometer on swing eccentric hamstring exercise measures in soccer players

Abstract: Background The use of a functional electromechanical dynamometer (FEMD) has been proposed as a valid and effective tool to evaluate specific movement patterns. The aim of this study was to determine the reliability of FEMD on swing eccentric hamstring exercise (SEHE) measures in soccer players. Methods Nineteen federated male soccer players (20.74 ± 4.04 years) performed the SEHE at three different isokinetic velocities (20–40–60 cm/s). These evaluations were conducted in four sessions, two for familiarizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…This occurs in all the variables evaluated in the two squat protocols performed in this study, so according to Weir [31], this threshold was met for all our outcome variables. These high-reliability values are due to two main reasons: (1) the high accuracy of the FEMD used, as previously stated [20,23,25,36] and…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This occurs in all the variables evaluated in the two squat protocols performed in this study, so according to Weir [31], this threshold was met for all our outcome variables. These high-reliability values are due to two main reasons: (1) the high accuracy of the FEMD used, as previously stated [20,23,25,36] and…”
Section: Discussionmentioning
confidence: 80%
“…Moreover, it has been shown to be a valid and reliable evaluation method [22,23]. This technology has been used to study the strength of different exercises and has obtained high-reliability values [20,[23][24][25][26]. However, the reliability of the squat has not been evaluated with this device.…”
Section: Introductionmentioning
confidence: 99%
“…Our research has shown that the use of specific strength assessment tests, the FDST, together with field tests, the SPT, is useful for the trainer or researcher to know the operational status of the athlete at a given time without deviating too much from the specific preparation objective, since these tests are suitable to evaluate and improve performance at the same time. In this research, FDSTs could be applied thanks to the use of the DEMF, a new device that allows evaluating and training strength in natural conditions [34,[47][48][49][50].…”
Section: Practical Applicationsmentioning
confidence: 99%
“…El desarrollo de la tecnología ha ofrecido la posibilidad de comenzar a trabajar con dinamómetros electromecánicos funcionales (DEMF), que permiten dar un salto de calidad al trabajo específico de fuerza. Gracias a esto, se solventa el vacío existente entre el control del trabajo de fuerza específico y su aplicación al gesto real del juego, permitiendo una evaluación y entrenamiento en condiciones funcionales (Jerez-Mayorga et al, 2021;Martínez-García et al, 2021;Rodriguez-Perea et al, 2021;Sánchez-Sánchez et al, 2021). El trabajo con DEFM permite controlar las diferentes variables durante los gestos específicos de un deporte concreto, como la carga, el rango la velocidad de movimiento, la magnitud de resistencia, y el tipo de contracción muscular (isométrica, concéntrica y excéntrica).…”
Section: Introductionunclassified